Pengaruh Online Customer Review dan Rating Media Online Shopee terhadap Minat Beli Konsumen Brand Erigo - Muhamad Reza Mauli; Zulfebriges (Jurnal Riset Manajemen Komunikasi, 2022)
In times like this, access to information is very necessary, without world information such as stopping to look for information related to things of daily needs such as clothing, food and shelter in an era like this Online Media seems to be a necessity that is close to humans. Because all related information is displayed on online media, online media such as directions on a trip, we can find out a lot of information every day. Starting from shopping online in times like this, such as E-commerce that is present like Shopee, we can find out a lot of information related to the products we want to buy. The Review and Rating features in Shopee's E-commerce have also been applied in many other E-commerce, because it seems important and interesting for potential consumers in determining product purchases, because we can share information about goods or subjects such as Brand Erigo which working in the clothing line world where researchers want to prove by conducting a study entitled "The Effect of Online Customer Reviews and Ratings on Buying Interest in Erigo Brand" which researchers want to prove how influential the information presented in Online Customer Reviews and Ratings is. This study uses a quantitative method with a simple linear regression approach, using a random sampling technique. This study took 100 respondents, Screeen Quisoner and obtained from the results of primary data and secondary data, from the results of the hypothesis obtained from the partial t test that accepted H1 and H2 that Online Customer Reviews and Ratings have a positive effect on buying interest, where this study also functions to knowing the market in the Banten area, where the data is also to find out to what extent the influence of Online Customer Reviews and Ratings on the Erigo Brand in the Banten area.